2003
DOI: 10.1007/s11906-003-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and blood pressure regulation

Abstract: Thyroid hormone has well-recognized effects on the cardiovascular system and blood pressure regulation. Blood pressure is altered across the entire spectrum of thyroid disease. The effects of hyperthyroidism include increased cardiac output, contractility, tachycardia, widened pulse pressure, decreased systemic vascular resistance, and increased basal metabolic rate. The manifestations of hypothyroidism are in marked contrast to those of hyperthyroidism and include decreased cardiac output, narrow pulse pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
127
3
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 81 publications
1
127
3
5
Order By: Relevance
“…55,56 Thyroid hormone increases basal metabolic rate in almost every tissue and organ system in the body, and the increased metabolic demands lead to changes in cardiac output, SVR, and blood pressure ( Figure 2). 54 In many regards these changes are similar to the physiological response to exercise. 54,57 A widened pulse pressure is characteristic of hyperthyroidism.…”
Section: Thyroid Hormone Effects On Blood Pressure Regulationmentioning
confidence: 86%
See 4 more Smart Citations
“…55,56 Thyroid hormone increases basal metabolic rate in almost every tissue and organ system in the body, and the increased metabolic demands lead to changes in cardiac output, SVR, and blood pressure ( Figure 2). 54 In many regards these changes are similar to the physiological response to exercise. 54,57 A widened pulse pressure is characteristic of hyperthyroidism.…”
Section: Thyroid Hormone Effects On Blood Pressure Regulationmentioning
confidence: 86%
“…54 In many regards these changes are similar to the physiological response to exercise. 54,57 A widened pulse pressure is characteristic of hyperthyroidism. Recent reports have shown that arterial stiffness is increased in hyperthyroidism despite the low SVR.…”
Section: Thyroid Hormone Effects On Blood Pressure Regulationmentioning
confidence: 86%
See 3 more Smart Citations